The ecosystem pathway: Transforming university incubation into entrepreneurial outcomes - Dahrul Siregar; Agus Salim Harahap; Wan Suryani (Faculty of Economics and Business, University of Muhammadiyah Malang, 2026)
Entrepreneurship is increasingly recognized as a driver of economic resilience and competitiveness, particularly in emerging economies such as Indonesia. Despite government initiatives, the national entrepreneurship ratio remains below regional benchmarks, underscoring the need for effective mechanisms to nurture student entrepreneurship. Universities play a critical role through incubation programs, yet empirical evidence on their effectiveness remains limited in the Indonesian context. This study develops and empirically tests a comprehensive incubation model that integrates three dimensions—resources, services, and institutional support—while examining the mediating role of the entrepreneurial ecosystem. Using survey data from 200 Indonesian university students who participated in incubation or entrepreneurship development programs, the analysis employs baseline Ordinary Least Squares (OLS) regression and mediation testing with bootstrapping. The findings reveal that services exert both direct and indirect effects on entrepreneurial outcomes, while resources and institutional support influence outcomes only indirectly through the ecosystem. The entrepreneurial ecosystem itself emerges as the strongest predictor, consolidating incubation inputs into enhanced entrepreneurial intention, competence, and behavior. Theoretically, the results extend the Resource-Based View (RBV) and social capital theory by showing that incubation inputs must be embedded in an ecosystem of networks and culture to generate impact. Practically, the study underscores the need for Indonesian universities and policymakers to strengthen incubation services, transform resources and institutional support into ecosystem-building mechanisms, and adopt ecosystem-oriented strategies in higher education policy.